2017
DOI: 10.2196/jmir.6336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Web-Based Health Information in Help-Seeking Behavior Prior to a Diagnosis of Lung Cancer: A Mixed-Methods Study

Abstract: BackgroundDelays to diagnosis in lung cancer can lead to reduced chance of survival, and patients often wait for several months before presenting symptoms. The time between first symptom recognition until diagnosis has been theorized into three intervals: symptom appraisal, help-seeking, and diagnostic interval (here: “pathway to diagnosis”). Interventions are needed to reduce delays to diagnosis in lung cancer. The Web has become an important lay health information source and could potentially play a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…We aimed to recruit people with potential lung cancer symptoms and proxies searching on their behalf, as a previous study indicated that others often research symptoms on behalf of patients with lung cancer (Mueller, Jay, Harper, & Todd, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We aimed to recruit people with potential lung cancer symptoms and proxies searching on their behalf, as a previous study indicated that others often research symptoms on behalf of patients with lung cancer (Mueller, Jay, Harper, & Todd, ).…”
Section: Methodsmentioning
confidence: 99%
“…Individuals often research their symptoms prior to presentation to health services, and this can impact on decisions to seek help (Mueller et al ., ). Moreover, recent research shows some people with lung cancer report researching their symptoms online prior to being diagnosed, and this seems to affect decisions of whether to present to health services and whether to request further diagnostic tests (Mueller, Jay, Harper, & Todd, ). Thus, targeting online health information could influence lung cancer symptom awareness and delays to diagnosis, ultimately improving chances of survival.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of conflicting information on a health topic, individuals actively and preferentially access information that reinforces their beliefs while avoiding information that challenges their beliefs [12]. Similarly, research has shown that internet users' search strategies are systematically biased towards examining only the top search results from search engines and following links related to more serious health conditions when trying to self diagnose [13]. Despite these biases, Internet users tend to believe the information they find online is accurate and trustworthy, regardless of the actual accuracy of the information [14].…”
Section: Introductionmentioning
confidence: 99%